Detection of Hepatitis B Virus DNA among Chronic and potential Occult HBV patients in resource‐limited settings by Loop‐Mediated Isothermal Amplification assay. Issue 11 (20th June 2018) - Akram, A.; Islam, S. M. R.; Munshi, S. U.; Tabassum, S.
Summary: Transmission of Hepatitis B Virus (HBV) usually occurs due to the transfusion of blood or blood products from chronic HBV (CHB) or occult HBV‐infected (OBI) patients. Besides serological tests, e.g. HBsAg and anti‐ HBc (total), detection of HBVDNA is necessary for the diagnosis of OBI patients. Different nucleic acid tests (NATs) including real‐ time–Polymerase Chain Reaction (qPCR) are used to detect HBV‐ DNA. The NATs are expensive and require technical expertise which are barriers to introduce them in resource‐limited settings. This study was undertaken to evaluate the use of Loop‐Mediated Isothermal Amplification (LAMP) assay as an alternative to qPCR for the detection of HBV‐DNA in CHB and potential OBI patients in resource‐limited settings. Following the published protocols with some modifications, a LAMP assay was developed for detection of HBV‐DNA by either using a heat block followed by detection in an agarose gel or using a qPCR thermocycler. The LAMP assay was applied to supernatant prepared from heat‐treated serum collected from CHB and potential OBI patients. HBV viral load in serum was measured by qPCR using a single‐step HBV‐DNA quantification kit. Among 200 samples tested, qPCR was capable to detect HBV‐DNA in 25.5% of cases, whereas LAMP assay detected HBV‐DNA in 43.5% cases. The qPCR was able to detect 11 (9.16%) potential OBI cases, whereas LAMP assay identified HBV‐DNA in 43 (35.83%) cases. In addition to tests for HBsAg and/or anti‐HBc (total), detection of HBV‐DNA by LAMP assay may aid in preventing post–transfusion HBV infection in resource‐limited settings.